Miért nem keresnek állást a Magyar munkanélküliek? Hipotézisek az Európai munkaerőfelvétel adatai alapján - János Köllő (Hungarian Academy of Sciences, Institute of Economics, 2009)
– The low level of job search is a unique feature of the Hungarian labour market compared to other former communist countries. The paper looks at search intensity among the non-employed using micro-data of the European Labour Force Survey. A section comparing Hungary, Poland and Slovakia in detail finds that Hungary's position is most probably explained by its special system of unemployment assistance. The majority of the non-employed, including those aged 15-59, receive disability pension or child-care benefit and, as a result, few of them are registered in the jobcentres. In addition, few of those who are registered look for jobs actively. While registration practices and job search among the registered unemployed differ substantially across the three countries considered, the linkages between job search, on the one hand, and education, gender, age or the duration of joblessness, on the other, are similar. The question of whether higher registration is conducive to more search is analysed using a quasi-panel of European countries. The estimates provide some support to the view that search intensity is more responsive to positive and negative shocks in countries, where the registration rate is higher.
Keywords: J64; J68; 330; unemployment; inactivity; job search; registration; Arbeitsuche; Arbeitslosigkeit; Ungarn